PROSESI BAIAT JAMA’AH TAREKAT SATTARIYYAH, PAJU, PONOROGO (Sebuah Kajian Fenomenologi) - Wahyudi Setiawan (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2015)
In Sufism, the congregation became a tradition for people who have the intention of themselves to the path of spiritual cleansing. Each congregation has a tradition, the system, as well as its own technical dhikr different between one another congregation, is no exception congregation Syattariyyah or more precisely referred to as the Jamaat Tawhid. This study uses a model kualititatif study using a phenomenological paradigm. Data collection was done by observation pastisipan–active, in-depth interviews, and documentary, which will produce a valid field data and measurable. Tradition rooster slaughter committed by Jamaat Tawhid is a process for the exercise of sacrifice, that is to sacrifice what he loves, in this case everything other than God. Sacrifice aims to empty the heart of earthly things that can interfere with the spiritual pilgrims on their way to God. This procession contains a spiritual meaning associated with each individual pilgrims.